Medicare Advantage: A Disadvantage for Complex Cancer Surgery Patients. Issue 6 (20th February 2023) - Raoof, Mustafa; Ituarte, Philip H.G.; Haye, Sidra; Jacobson, Gretchen; Sullivan, Kevin M.; Eng, Oliver; Kim, Jae; Fong, Yuman
Abstract : PURPOSE: Nearly half of all Medicare beneficiaries are enrolled in privatized Medicare insurance plans (Medicare Advantage [MA]). Little comparative information is available about access, outcomes, and cost of inpatient cancer surgery between MA and Traditional Medicare (TM) beneficiaries. We set out to assess and compare access, postoperative outcomes, and estimated cost of inpatient cancer surgery among MA and TM beneficiaries. METHODS: Retrospective cohort analysis of MA or TM beneficiaries undergoing elective inpatient cancer surgery (for cancers located in lung, esophagus, stomach, pancreas, liver, colon, or rectum) was performed using the Office of Statewide Health Planning Inpatient Database linked to California Cancer Registry from 2000 to 2020. For each cancer site, risk-standardized access to high-volume hospitals, postoperative 30-day mortality, complications, failure to rescue, and surgery-specific estimated costs were compared between MA and TM beneficiaries. RESULTS: This analysis of 76, 655 Medicare beneficiaries (median age 74 years, 51% female, 39% MA) included 31, 913 colectomies, 10, 358 proctectomies, 4, 604 hepatectomies, 2, 895 pancreatectomies, 3, 639 gastrectomies, 1, 555 esophagectomies, and 21, 691 lung resections. Except for colon surgery, MA beneficiaries were less likely to receive care at a high-volume hospital. Mortality was significantly higher among MA beneficiaries ( v TM) for gastrectomy (adjusted risk difference [ARD], 1.5%; 95% CI, 0.01 to 2.9; P = .036), pancreatectomy (ARD, 2.0%; CI, 0.80 to 3.3; P = .002), and hepatectomy (ARD, 1.4%; 95% CI, 0.1 to 2.9; P = .04). By contrast, compared with TM, MA beneficiaries incurred lower estimated hospital costs. CONCLUSION: Enrollment in MA plan is associated with lower estimated hospital costs. However, compared with TM, MA beneficiaries had lower access to high-volume hospitals and increased 30-day mortality for stomach, pancreas, or liver surgery.